THE LIGAMENT OF BARKOW IS A SOLID STRUCTURE IN HUMAN FETUSES - JOãO PEDRO MORAES MIOSSI; JOSEMBERG DA SILVA BAPTISTA (Coluna/Columna, 2023)
ABSTRACT Objective: The present study aims to dissect and identify the Barkow ligament (LB) in fetal specimens and describe its anatomical characteristics to contribute to its knowledge in the pediatric population and the clinical and surgical application of conditions associated with the Craniovertebral Junction (CVJ). ). Methods: This work evaluated 19 human fetuses aged 28-38 weeks. Of these, six specimens constituted the final sample and were studied through detailed dissections using coronal sections in an anterior approach up to the region described by the LB. Results: In all specimens, a thin fibrous band was found, horizontal and anterior to the axis tooth, with bilateral fixation on the occipital condyles, corroborating the results found for describing LB in adults. Conclusion: The LB is a congenital ligament that resists the extension of the atlantooccipital joint and may play a role in the stability of the CVJ. Level of Evidence III; Diagnostic Study.